Effect of Water Exchange and Mechanical Aeration on Grow-out of the Amazon River Prawn in Ponds - Kimpara, Janaina M.; Santos, Alexandre A. O.; Valenti, Wagner C. (Wiley-Blackwell, 2013)
Exchange and aeration of pond water are common practices in semi-intensive freshwater prawn culture, but there is lack of scientifically based information on the results. We evaluated the effects of water flow through the ponds and mechanical aeration in semi-intensive cultures of Macrobrachium amazonicum. A total of 40 juveniles/m(2) were stocked for 4 mo in 12 earthen ponds. Four randomly assigned treatments were applied: no aeration+no water exchange (NN), diurnal aeration+no water exchange (DA), nocturnal aeration+no water exchange (NA), and continuous water flow (CF). Temperature, pH, total suspended solids, and soluble orthophosphate in the water column did not differ among treatments. Dissolved oxygen (DO) concentrations in ponds with nocturnal aeration were significantly higher than in other treatments. The concentration of inorganic nitrogen was significantly higher in the CF treatment, whereas organic nitrogen was higher in treatments NN, DA, and NA. This suggests that primary production is higher in static ponds. Thermal stratification started at 0900 h, and the maximum difference between surface and bottom temperature varied from 1.5 (CF) to 2.8 C (NN). The difference between DO levels in the surface and bottom water of the ponds began to appear at 0800 h and varied from 0.50 (CF) to 5.23 mg/L (NN). Diurnal aeration and high continuous water flow were efficient in disrupting the stratification. No significant difference was found for survival, mean weight, apparent feed conversion rate, and productivity among treatments. Thus, disrupting water stratification, aerating ponds at night, or exchanging the pond water are ineffective in Amazon River prawn farming in semi-intensive systems, at least for stocking densities lower than 40 individuals/m(2). About 1000 kg of Amazon River prawn can be produced in static ponds with no aeration in approximately 4 mo. This management strategy saves water and energy and reduces production costs.